2015
DOI: 10.1039/c4cc09277e
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant free superparamagnetic iron oxide nanoparticles for stable ferrofluids in physiological solutions

Abstract: A process is reported to obtain a nanoparticle sol from co-precipitated iron oxide particles without using any surfactant. The sol - a true ferrofluid - is not only stable over a wide range of pH but also in physiological solutions. This is a decisive step towards biomedical applications where nanoparticle agglomeration could so far only be prevented by using unwanted surfactants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 36 publications
4
35
0
Order By: Relevance
“…Thus, it can only be stated that hints were found that the zeta potential of the supraparticle system seems to behave as expected from a mix of the two nanoparticle constituents. This is likely and could be demonstrated on a single particle level in case of an iron oxide nanoparticle core with silica patches by us recently, i. e ., there, it was shown that the zeta potential versus pH curve of the iron oxide core @ silica patches system was somewhat in‐between the curves of pure iron oxide and pure silica, correlating to the fractions of the two constituents …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, it can only be stated that hints were found that the zeta potential of the supraparticle system seems to behave as expected from a mix of the two nanoparticle constituents. This is likely and could be demonstrated on a single particle level in case of an iron oxide nanoparticle core with silica patches by us recently, i. e ., there, it was shown that the zeta potential versus pH curve of the iron oxide core @ silica patches system was somewhat in‐between the curves of pure iron oxide and pure silica, correlating to the fractions of the two constituents …”
Section: Resultsmentioning
confidence: 99%
“…Compared to other adsorber systems reported in literature, the specific surface area is about average. [15][16][17][18][19] Adsorbers with higher surface area such as 1380 m 2 /g and 2134 m 2 /g were reported as well. [6,5] Yet, the approach reported herein comes with all the flexibility to build a system of desired composition, e. g. in terms of silica nanoparticle amount and size and magnetic nanoparticle content, in a completely flexible, "Lego building block like" manner (compare Scheme 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 In addition, Fe 3 O 4 magnetic nanoparticles (MNPs) have shown promising application as materials of interest for ferrofluids, 3,4 hyperthermia, 5 magnetic resonance imaging (MRI), 6,7 high-density information storage, 8 and targeted drug delivery labeling. 9 A variety of methodologies including coprecipitation, sol-gel method, thermal decomposition, microemulsion and hydrothermal synthesis have been reported for the synthesis of Fe 3 O 4 MNPs, and further advancement in the synthesis of such materials is still on-going due to their outstanding potential in variety of applications.…”
Section: Introductionmentioning
confidence: 99%
“…Our preferred particle materials are inorganic and hybrid materials, e.g. materials based on silicate, calcium fluoride and phosphate, TiO2 and iron oxide [1,2]. To ensure multifunctionality, different approaches are taken: the labelling of the NP matrix with organic dyes or lanthanide ions, as well as the combination of various materials by core-shell NP design.…”
mentioning
confidence: 99%